Petrarch and the Vision of Rome - Unn Falkeid (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2017)
Petrarch’s enthusiasm for the eternal city is balanced by a deep sense of perishability and death. Both visions – the Classical and the Augustinian – are fused into a double perspective in Petrarch’s description of Rome, transformed both by the harsh political conditions of the fourteenth century as well as the author’s personal experiences. This double perspective articulates an ambiguity most familiar to modern scholars of history: while Petrarch was trying to retrieve Classical art and virtues, he also emphasized the falseness of the reconstruction of Rome as an ideal ancient city and the impossibility of catching the echoes petrified in the many ruins and fragments of the past.